Effect of the microhardness difference between base metal and bionic coupling unit on wear resistance of gray cast iron. (December 2015) - Pang, Zuobo; Zhou, Hong; Chang, Fang; Zhang, Peng; Cong, Dalong; Meng, Chao; Wang, Chuanwei; Ren, Luquan
Abstract: In order to improve the wear resistance of gray cast iron guide rail, the samples with different microhardness difference between bionic coupling units and base metal were manufactured by laser surface remelting. Wear behavior of gray cast iron with bionic coupling units has been studied under dry sliding condition at room temperature using a homemade liner reciprocating wear testing machine. The wear resistance was evaluated by means of weight loss measurement and wear morphology. The results indicated that when the microhardness difference is 561 HV0.2, the wear resistance of sample is the best. Highlights: Bionic coupling surface is beneficial to improve wear resistance of gray cast iron. The liner reciprocating behavior of bionic coupling samples was studied. When the microhardness difference is 561 HV0.2, the wear resistance is the best.